2010
DOI: 10.1002/syn.20837
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic morphology of neurons in medial prefrontal cortex, hippocampus, and nucleus accumbens in adult SH rats

Abstract: We have studied, in spontaneously hypertensive (SH) rats at different ages (2, 4, and 8 months old), the dendritic morphological changes of the pyramidal neurons of the medial prefrontal cortex (mPFC) and hippocampus and medium spiny neurons of the nucleus accumbens (NAcc) induced by the chronic effect of high-blood pressure. As control animals, we used Wistar-Kioto (WK) rats. Blood pressure was measured every 2 months to confirm the increase in arterial blood pressure. Spontaneous locomotor activity was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 81 publications
1
45
0
1
Order By: Relevance
“…Dendrite development involves dendrite and spine growth followed by higher order branching and spine maturation (Koss et al 2014; Lu et al 2013; Maynard et al 2012; Verslegers et al 2014). Slight decreases in spine density have been reported with age in areas such as the mPFC, Acb and hippocampus (Sánchez et al 2011), and are supported by the present study. In situ hybridization histochemical studies demonstrated that CB1r expression in prefrontal cortex follows distinct trajectories (Heng et al 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Dendrite development involves dendrite and spine growth followed by higher order branching and spine maturation (Koss et al 2014; Lu et al 2013; Maynard et al 2012; Verslegers et al 2014). Slight decreases in spine density have been reported with age in areas such as the mPFC, Acb and hippocampus (Sánchez et al 2011), and are supported by the present study. In situ hybridization histochemical studies demonstrated that CB1r expression in prefrontal cortex follows distinct trajectories (Heng et al 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Alterations in dendritic and/or spine morphology have been correlated in hypertension (Sanchez et al, 2011; Vega et al, 2004) including in PVN-RVLM circuits (Sonner et al, 2008). Thus, the morphology of RVLM dendritic profiles was assessed in male and female mice.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, we did not include an age-matched control group as age-related changes in dendritic morphology develop over several years [29] -within the 1 to 2 months that are relevant four our study, no changes in dendritic morphology are expected [30,31]. Only a non-significant trend is observed for increased dendritic length at 30 days (SRT+30).…”
Section: Methodological Considerationsmentioning
confidence: 99%